DATA MINING PENGELOMPOKKAN PEMAKAIAN LISTRIK TERBOROS MENGGUNAKAN METODE CLUSTERING (STUDI KASUS PLN AREA BINJAI) - Manik, Ediman (Journal Information System Development (ISD), 2018)
-- Clustering is a method used to classify a set of objects into classes consisting of the same objects. In other words clustering is the process of grouping objects based on the similarity of characteristics among the objects. In this thesis will be discussed about the clustering method by using K-Means algorithm that is used to determine the value of the electricity usage group as well as grouping it based on the level of power usage and the hours of the flame so that it can be grouped and known which ones are lost. The K-Means algorithm is one of the clustering methods that researchers will use to solve the problem of grouping. Starting from the determination of the grouping boundaries to the determination of each cluster so that the groups formed the data of electricity consumption adjusted with the level of usage. The result of this thesis is the value of data grouped by level of electricity usage grouping. And with the support of GUI programming MATLAB expected this program can be used easily. With this application can be seen the results of 200 data for cluster 1 as much as 44 with the Group of use of electricity in the group at the address is Binjai Timur and for Power group 450 and Jam on> 1100 and Cluster 2 as many as 60 Users of the listik peloros at the address group is Binjai Kota and for Power 450 and 901-1100 Clock 3 and 96 for cluster 3 groups with License usage groups in the Address group are North Binjai and for Daya Power 450 and Jam 700-900.Keywords: Clustering, Electricity Usage